Sustainable Seismic Energy Assessment of Italian Residential Heritage in Reinforced Concrete with Masonry Infills: An HBIM Evaluation Tool - Lisa Bonaguidi; Claudio Sebastiani; Silvia Santini (Buildings)
Design is a multidisciplinary subject; it cannot and should not admit one-way visions, and today, more than ever, there is a need for collaboration among all the specialized technicians to immediately consider all the issues, in particular the combination of energy efficiency and seismic protection. This article aims to demonstrate how the HBIM workflow can be applied to data collection, mapping, modeling, and analyses, providing a methodology that can be valid and efficient for different public administrations, aimed at creating an open database (Open HBIM) accessible at any time to constantly monitor and update the data and interventions on existing buildings. The results will be “integrated” with models, which can provide data for specific evaluations. As an application of the HBIM methodology, the structural and energy infill performance of Italian buildings were investigated, with reference to four types of infill in reinforced concrete frames placed in four different Italian cities.